ASESMEN PARTISIPATIF MOTIVASIONAL PADA PROGRAM PEMBERDAYAAN MASYARAKAT DI YAYASAN USAHA MULIA CIANJUR JAWA BARAT - Haitami, Haitami; Aribowo , Aribowo; Gaol, Harapan Lumban (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
This research focuses on social work technology engineering efforts with poverty on the changing profile of communities. One technology that is often used is Methodology Participatory Assessment (MPA) which aims to identify problems, needs and strengths of society in a participatory manner. However, the use of MPA does not guarantee the success of a program because it does not touch the motivational aspects of benefit recipients so that it has an impact on the sustainability of the program being run. Departing from this, it encourages researchers to adapt several methods to improve the current MPA. The research method used is a qualitative method with a Participatory Action Research (PAR) approach. This research attempts to combine the MPA method with motivational interviews (MI) into a motivational participatory assessment which can be used as an alternative in conducting assessments in community change programs at the Mulia Enterprise Foundation (YUM). MI is effective in generating thoughts, feelings and actions towards change and this includes readiness to make changes towards more sustainable options. This research involved Social Workers, YUM employees and beneficiaries using data collection techniques through in-depth interviews, observations, focus group discussions and documentation studies. The research begins with reflection on the initial model, then formulates the need for model improvement and designs the model according to the needs of the research locus. After the model is formed, the model design is implemented at the research locus and ends with an evaluation to obtain recommendations for a better model. The results of implementing the motivational participatory assessment technology engineering model are able to optimize participatory assessment by increasing the motivation of beneficiaries to increase awareness towards sustainable change.